Le mouvement étudiant et la question des langues en Algérie (1962-1965) : à propos d’un épisode méconnu de l’histoire de l’UGEMA-UNEA - Yassine Temlali (L’Année du Maghreb)
In Algeria in 1963, a year after the disappearance of the chair of Berber in the wreck of the colonial university, there was a brief flourishing of student demands for the “development of the Kabyle language” and the “creation of an institute for the teaching of Berber”. Formulated by a commission of the Fifth Congress of the Union générale des étudiants musulmans algériens (UGEMA), these were immediately abandoned without ever being submitted to the plenary session. In reconstructing this obscure episode in the light of many sources, including the accounts of participants, this article explores the attitude of the student movement, in the immediate post-independence period (1962–1965), to the question of Berber languages, which were spoken by a fifth of the population but which at the time enjoyed no explicit juridical status. It looks more generally at the positions of this movement on the linguistic problem in Algeria in a context in which the promotion of the “national language”, Arabic, had to reckon with the first questioning of the Arabo-Islamic unanimity imposed by the need for unity against the French occupier.I suggest that the burial of these proposals in favour of Berber languages should be interpreted in the light of the cultural doctrine of the Algerian Communist Party (PCA), then dominant within the framework of the UGEMA, and its general attitude towards the “socialist” regime of Ahmed Ben Bella. While pleading in favour of the promotion/modernisation of Arabic, the PCA recommended the protection not only of French but also of Kabyle, regionalist threats having been removed with the coming of independence. Inherited from the era in which it considered Algeria as a great ethnocultural mosaic, the party’s benevolence towards mother tongues was, nevertheless, confronted by the necessities of its support for the regime, which suspected the demand for recognition of the Berber-speaking community to conceal a project of national division. The PCA’s support for Ben Bella, which went so far as the wish to dissolve into a single great revolutionary party, extended its link with the radical nationalists begun in the late 1940s, radicalised during the War of Liberation (1954–1962) and pursued after 1962. It manifested itself in different forms within the ranks of the UGEMA, which came under communist influence from early 1963. This organisation would adhere to the programme of the FLN, established in 1962 as a single party, and mobilised students in support of the initiatives of the government (joint worker-management control, nationalisation, etc.), notably through voluntary service campaigns. In return, its organic autonomy was generally tolerated by the FLN, and it received subsidies and logistical support.The burial of proposals in favour of Berber languages at the Fifth Congress of the UGEMA would also carry the mark of the alliance of the communists with Ahmed Ben Bella. The openness to multilingualism by the communist cadres of this organisation would have been contradicted by the PCA’s commitments to the regime. Occurring amid the split in the student movement over the pace and priorities of Arabisation, this evasion would have been made easier by another factor: in newly independent Algeria, the minority status of non-written languages was assumed as a matter of course, so much so that only a few intellectuals demanded their recognition. From this viewpoint, the scotching of these proposals before they reached the plenary of the Fifth Congress did not spoil a certain harmony between the communists and the regime over the linguistic problem. Centred on a promotion/modernisation of Arabic that did not sacrifice the French-speaking community, the positions of the PCA in this area corresponded to official language policy. This, in spite of Ahmed Ben Bella’s declarations of Arabist principles, would work objectively not towards the defrancisation of the state and society but rather towards its bilingualisation through a measured promotion of Arabic.By contextualising as fully as possible a little-recognised mini-episode from the Fifth Congress of the UGEMA – and by illuminating, through this episode, the positions of the organisation on the linguistic question – this article emphasises the importance of university cultural debates for a better understanding of both the history of the Algerian student movement and the Berber claim in Algeria.